Balance Assessment of Children with Sensorineural Hearing Loss - Apeksha, Kumari (Indian J Otolaryngol Head Neck Surg, 2020)
This study aimed to assess the balance function in children with sensorineural hearing loss (SNHL) using different tests to assess vestibulospinal pathway and tests to assess vestibular system and to compare the result obtained with those of children with normal hearing sensitivity. Detailed balance assessment was done for 15 children with severe to profound SNHL and 15 children with normal hearing sensitivity in the age range of 6–10 years. The audiological evaluation included pure-tone audiometry, speech audiometry, immittance evaluation, otoacoustic emission, vestibular evoked myogenic potential (cervical VEMP and ocular VEMP), and tests to assess vestibulospinal pathway and cerebellar function, such as Romberg test, Fukuda stepping test, Tandem gait test, and Finger-to-nose test. cVEMP and oVEMP were absent in 8 ears (27%) of a total of 30 ears with SNHL. Statistical analysis shows no significant difference between latency and amplitude of cVEMP peaks and latency of oVEMP peaks across groups. Significant reduction of oVEMP peaks amplitude was seen in children with SNHL compared to children with normal hearing. Fukuda stepping test showed an abnormal response in 2 children with SNHL (13%) and one child could not perform tandem gait test (7%). Children with SNHL showed an evident abnormality on the balance assessment test results. The abnormal function of the vestibular system and the vestibulospinal pathway can compromise the child’s motor development and thus needs investigation early in life.